Intracellular monitoring of NADH release from mitochondria using a single functionalized nanowire electrode. Issue 33 (7th August 2020) - Jiang, Hong; Qi, Yu-Ting; Wu, Wen-Tao; Wen, Ming-Yong; Liu, Yan-Ling; Huang, Wei-Hua
Abstract : A single nanowire NADH sensor with excellent electrochemical and antifouling performance is fabricated, and glucose- and resveratrol (a natural product compound)-induced NADH release from intracellular mitochondria is successfully investigated. Abstract : Mitochondria are the powerhouse of cells, and also their suicidal weapon store. Mitochondrial dysfunction can cause the opening of the mitochondrial permeability transition pore (mPTP) and nicotinamide adenine dinucleotide (NADH) release from mitochondria, eventually leading to the disruption of energy metabolism and even cell death. Hence, NADH is often considered a marker of mitochondrial function, but in situ monitoring of NADH release from mitochondria in single living cells remains a great challenge. Herein, we develop a functionalized single nanowire electrode (NWE) for electrochemical detection of NADH release from intracellular mitochondria by modifying conductive polymer (poly(3, 4-ethylendioxythiophene), PEDOT)-coated carbon nanotubes (CNTs) on the surface of a SiC@C nanowire. The positively charged PEDOT facilitates the accumulation of negatively charged NADH at the electrode surface and CNTs promote electron transfer, thus endowing the NWE with high sensitivity and selectivity. Further studies show that resveratrol, a natural product, specifically induced NADH release from mitochondria of MCF-7 cancer cells rather than non-cancerous MCF-10 A cells, indicating the potential therapeutic effects of resveratrol in cancer treatment. This work provides an efficient method to monitor mitochondrial function by in situ electrochemical measurement of NADH release, which will be of great benefit for physiological and pathological studies.